The effect of autumn N supply on the architecture of young peach (Prunus persica L.) trees - Jordan, Marie-Odile; Wendler, Renate; Millard, Peter (Trees (Berlin, West), 2009)
Irrigation and fertilisation were recently considered as useful tools to control tree shape, and reduce pruning costs. The role of the N reserves, which determined spring growth, was considered to be essential. We intended therefore to evaluate its effects on peach tree architecture. Four levels of N fertilisation were applied on 1-year-old trees, from the end of shoot growth to leaf fall. In subsequent spring, each bud fell into one of the ten classes of positions previously defined within the crown. Its development was followed weekly from burst to June. Fertilisation promoted growth until a threshold level, since no differences were evidenced between the three highest N treatments. Fall N did not affect burst but the further transformation of the buds into rosettes, proleptic or ramificated axes. Crown base was little affected. Fall N increased the number of proleptic axes on most median and upper positions. Axes lengthening and thickening were limited on the median positions, promoted at crown top. The variations concerned the mean internodes lengths, not the number of phytomers per axis. Sylleptic ramification was limited to the crown outer parts, and decreased with fall N. Treatment did neither affect the fruit dry weights, nor the ratio between the number of leaves and the number of fruits. Fruit number was proportioned to vegetative growth by blossoming and fruit set. We conclude that a moderate autumn fertilisation improved orchard productivity, but favoured vegetative growth in the crown outer parts. Additional pruning may therefore be required to control tree shape.